Synthetic cannabinoids JWH-018, JWH-122, UR-144 and the phytocannabinoid THC activate apoptosis in placental cells. (1st February 2020) - Almada, Marta; Alves, Patrícia; Fonseca, Bruno M.; Carvalho, Félix; Queirós, Cláudio R.; Gaspar, Helena; Amaral, Cristina; Teixeira, Natércia A.; Correia-da-Silva, Georgina
Highlights: THC, JWH-018, JWH-122 and UR-144 affect the viability of placental trophoblasts THC, JWH-018, JWH-122 and UR-144 impair cell proliferation and induce apoptosis through different mechanisms The phytocannabinoid THC and the synthetic cannabinoids may disrupt fundamental gestational events Abstract: The increasing use of synthetic cannabinoids (SCBs) in recreational settings is becoming a new paradigm of drug abuse. Although SCBs effects mimic those of the Cannabis sativa plant, these drugs are frequently more potent and hazardous. It is known that endocannabinoid signalling plays a crucial role in diverse reproductive events such as placental development. Moreover, the negative impact of the phytocannabinoid Δ 9 -tetrahydrocannabinol (THC) in pregnancy outcome, leading to prematurity, intrauterine growth restriction and low birth weight is well recognized, which makes women of childbearing age a sensitive group to developmental adverse effects of cannabinoids. Placental trophoblast turnover relies on regulated processes of proliferation and apoptosis for normal placental development. Here, we explored the impact of the SCBs JWH-018, JWH-122 and UR-144 and of the phytocannabinoid THC in BeWo cell line, a human placental cytotrophoblast cell model. All the cannabinoids caused a significant decrease in cell viability without LDH release, though this effect was only detected for the highest concentrations of THC. Moreover, a cell cycle arrest at the G2 /M phase was also observed. JWH-018 and JWH-122 increased reactive oxygen species (ROS) production and THC, UR-144 and JWH-122 caused loss of mitochondrial membrane potential. All the compounds were able to induce caspase-9 activation. The involvement of apoptotic pathways was further confirmed through the significant increase in caspase -3/-7 activities. For UR-144, this effect was reversed by the CB1 antagonist AM281, for JWH-018 and THC this effect was mediated by both cannabinoid receptors CB1 and CB2 while for JWH-122 it was cannabinoid receptor-independent. This work demonstrates that THC and SCBs are able to induce apoptotic cell death. Although they may act through different mechanisms and potencies, the studied cannabinoids have the potential to disrupt gestational fundamental events.